2015
DOI: 10.1017/s0022029915000588
|View full text |Cite
|
Sign up to set email alerts
|

25-hydroxyvitamin D circulates in different fractions of calf plasma if the parent compound is vitamin D2or vitamin D3, respectively

Abstract: Vitamin D has become one of the most discussed nutrients in human nutrition, which has led to an increased interest in milk as a vitamin D source. Problems related to fortifying milk with synthetic vitamin D can be avoided by securing a high content of natural vitamin D in the milk by supplying dairy cows with sufficient vitamin D. However, choosing the most efficient route and form of supplementation requires insight into how different vitamin D metabolites are transported in the body of cattle. There are two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Vitamin D 2 is the most widely used form in supplements and fortified foods, while vitamin D 3 is the main dietary form (Borel et al, 2015). However, there is a controversy related to the biological equivalence of these two different types of vitamin D. Most studies state that vitamin D 3 supplementation is more effective in increasing serum levels of total 25(OH)D (G. R. Hart et al, 2006; Heaney et al, 2011; Houghton & Vieth, 2006; Hymoller & Jensen, 2016; Itkonen et al, 2016; Logan et al, 2013; Tripkovic et al, 2012, 2017; Wetmore et al, 2016), and some even claim that vitamin D 2 supplementation could reduce serum levels of 25(OH)D 3 (Biancuzzo et al, 2013; Lehmann et al, 2013; Stephensen et al, 2012) and should not be considered for supplementation or food fortification (Mistretta et al, 2008). Another study even found that supplementation of hens' diets with vitamin D 3 increased the vitamin D content of egg yolk more effectively than supplementation with vitamin D 2 (Mattila et al, 2004).…”
Section: Vitamin D Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D 2 is the most widely used form in supplements and fortified foods, while vitamin D 3 is the main dietary form (Borel et al, 2015). However, there is a controversy related to the biological equivalence of these two different types of vitamin D. Most studies state that vitamin D 3 supplementation is more effective in increasing serum levels of total 25(OH)D (G. R. Hart et al, 2006; Heaney et al, 2011; Houghton & Vieth, 2006; Hymoller & Jensen, 2016; Itkonen et al, 2016; Logan et al, 2013; Tripkovic et al, 2012, 2017; Wetmore et al, 2016), and some even claim that vitamin D 2 supplementation could reduce serum levels of 25(OH)D 3 (Biancuzzo et al, 2013; Lehmann et al, 2013; Stephensen et al, 2012) and should not be considered for supplementation or food fortification (Mistretta et al, 2008). Another study even found that supplementation of hens' diets with vitamin D 3 increased the vitamin D content of egg yolk more effectively than supplementation with vitamin D 2 (Mattila et al, 2004).…”
Section: Vitamin D Biologymentioning
confidence: 99%
“…Due to evidence indicating the greater effectiveness of vitamin D 3 over vitamin D 2 in increasing total 25(OH)D serum levels (Houghton & Vieth, 2006; Hymoller & Jensen, 2016; Itkonen et al, 2016; Logan et al, 2013; Tripkovic et al, 2012, 2017; Wetmore et al, 2016), it is logical to think that the first strategy to follow is the production of this molecule by yeast. Another aspect to consider is when the countries' food fortification policies only consider fortification with vitamin D 3 and not with vitamin D 2 , in which case it is necessary to produce the former.…”
Section: Vitamin D Production In Yeastmentioning
confidence: 99%
“…After ingestion with food or supplements and absorption in the gut, both vitamin D 2 and vitamin D 3 are transported via chylomicrons and DBP via the lymphatic system to the liver [63,64], where they are converted into their analogous metabolites, namely, 25(OH)D 2 and 25(OH)D 3 , similar to cutaneously produced vitamin D [63]. Finally, 25(OH)D produced in the liver enters the blood circulation, where it binds to DBP and lipoproteins [42].…”
Section: How Can a Healthy Vitamin D Status Be Achieved And Maintamentioning
confidence: 99%
“…Because of the low binding affinity, 25(OH)D 2 is also transported in chylomicrons and lipoprotein fraction 3 (LPF3). In contrast to DBP, chylomicrons and LPF3 fractions are not able to protect bound molecules against degradation or excretion [64]. It has been reported that in addition to the traditional pathway of ergosterol (similar to vitamin D produced in the skin), ergosterol can be hydroxylated by CYP11A1, first at the C24 position and second at C17, without side chain cleavage, resulting in 17α,24-dihydroxyergosterol (17α,24(OH) 2 D 2 ) [66].…”
Section: How Can a Healthy Vitamin D Status Be Achieved And Maintamentioning
confidence: 99%
“…Vit-D is then processed by the liver and kidney to make it beneficial for bones (4). Sunlight is a very important factor for Vit-D production (5), and Vit-D has two forms: Vitamin D 2 (Ergocalciferol) and vitamin D 3 (Cholecalciferol) (6). When human skin is exposed to solar UVB radiation (wavelengths: 290-315 nm), 7-dehydrocholesterol is converted in the skin first to preVit-D 3 , then from preVit-D 3 to Vit-D 3 .…”
Section: Introductionmentioning
confidence: 99%